2005
DOI: 10.1007/s00426-005-0220-2
|View full text |Cite
|
Sign up to set email alerts
|

The control of visual attention and its influence on prioritized processing in a location negative priming paradigm

Abstract: In a location-based negative priming paradigm, the possibility of a disengagement option of the underlying inhibitory mechanism was tested. Whereas in previous studies disengagement was observed when providing utility information about the probe trial structure, in the present study the allocation of visual attention to the stimuli was manipulated. In the first step an automatic deployment of visual attention was implemented by presenting all stimuli as abrupt onsets (Experiment 1), which demonstrated commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…Krueger et al (2007) investigated the role of attentional control in conflict processing by manipulation the onset mode of the stimuli. They found a behavioral NP effect for the onset but not for the masked stimulus condition (replicating results from Fischer & Hagendorf, 2006) associated with activations in the superior parietal cortex sensitive to these changes. Furthermore the authors could identify regions in the DLPFC and inferior parietal cortex to be involved in the conflict resolution indicating stronger attentional top-down modulations in the fronto-parietal network.…”
Section: Introductionmentioning
confidence: 55%
“…Krueger et al (2007) investigated the role of attentional control in conflict processing by manipulation the onset mode of the stimuli. They found a behavioral NP effect for the onset but not for the masked stimulus condition (replicating results from Fischer & Hagendorf, 2006) associated with activations in the superior parietal cortex sensitive to these changes. Furthermore the authors could identify regions in the DLPFC and inferior parietal cortex to be involved in the conflict resolution indicating stronger attentional top-down modulations in the fronto-parietal network.…”
Section: Introductionmentioning
confidence: 55%
“…In DT trials, the probe target appears at the location previously occupied by the prime distractor. DT trials result in increased response times, which are explained by additional distractor processing demands [7]–[8]. However, the nature of these control processes is under discussion [9].…”
Section: Introductionmentioning
confidence: 99%
“…As inhibitory processes decay gradually and do not dissolve with offset of the prime, inhibition of the prime distractor is still active at the time of probe presentation. For this reason the probe target must be presented in a certain timeframe to reveal a NP effect [7]. And probe targets of DT trials in comparison to control probe targets are particularly ‘weak’, because their identity/location are similar or even identical to those of the previously inhibited prime distractor.…”
Section: Introductionmentioning
confidence: 99%
“…In location tasks, participants also select a target on the basis of a particular physical attribute but are required to respond to a target location. As a general finding, research using location tasks failed to produce positive priming effects although clear negative priming effects have been reported (Buckolz et al, 2004;Park and Kanwisher, 1994; but see Fischer and Hagendorf, 2006). In contrast, with identification tasks positive priming is usually more reliable than negative priming (Lammertyn and Fias, 2005;Leboe et al, 2005;Malley and Strayer, 1995), although some studies have found subtle negative priming effects Lammertyn and Fias, 2005;Luna et al, 2006).…”
Section: Introductionmentioning
confidence: 88%
“…Cognitive variables have also shown to play an important role when attempting to explain processes involved in negative priming. In this regard, non-automatic control of attention makes negative priming to vanish as compared to conditions of automatic allocation of visual attention (Fischer and Hagendorf, 2006).…”
Section: Introductionmentioning
confidence: 99%